Equity Market Risk Premium and Global Integration - Johnson, Robert (2009)
The equity market risk premium remains one of the most debated issues in corporate finance. Monthly returns for 19 developed equity markets and 16 emerging equity markets between 1970 and 2006 aided in examining the extent of integration of these markets with the U.S. stock market and the Morgan Stanley Capital International (MSCI) World Index. Geweke measures of feedback indicate that although both developed and emerging markets show a slight and gradual increase in integration, emerging markets reflect significant segmentation from the U.S. stock market and the world market index. Greater stock market integration is associated with a more favorable economic and political climate toward business. Additional risk premiums relative to the intertemporal capital asset pricing model (ICAPM) arise because of segmentation of emerging markets from the world. Valuing business investments in countries with at least partially segmented equity markets requires an adjusted capital asset pricing model (CAPM).